Crystal Structures of Mycobacterium smegmatis RecA and Its Nucleotide Complexes - Datta, S. (American Society for Microbiology, 2003)
The crystal structures of Mycobacterium smegmatis RecA (RecA(Ms)) and its complexes with ADP, ATPγS, and dATP show that RecA(Ms) has an expanded binding site like that in Mycobacterium tuberculosis RecA, although there are small differences between the proteins in their modes of nucleotide binding. Nucleotide binding is invariably accompanied by the movement of Gln 196, which appears to provide the trigger for transmitting the effect of nucleotide binding to the DNA-binding loops. These observations provide a framework for exploring the known properties of the RecA proteins.